PERBANDINGAN SISTEM PEMERINTAHAN DI KOREA SELATAN, FILIPINA DAN INDONESIA DALAM PENERAPAN SISTEM PRESIDENSIAL - Rachmanto, Arif (Wacana Hukum, 2023)
The system of government will be reflected in the state constitution, Indonesian constitution is reflected in the UUD 1945. Although it does not explicitly mention, the constitution clearly shows the characteristics of the presidential system adopted by Indonesia. Some Asian countries also implement presidential systems of government such as in South Korea and Philippines. With different culture, will be different in the implementation of the presidential system of government, especially in terms of presidential elections, presidential accountability and the process of dismissing the president (impeachment). In the case of presidential elections, all are equally elected by the people, but only in Indonesia after the presidential term can still be re-elected. the president is accountable to the people of the state, except in South Korea, in addition to being responsible to the peopleof the state as well as to parliament because South Korea is a hybrid system in its system of government. In the process of dismissal of the president (impeachment) all countries involve legislative power except in Indonesia in addition to involving legislative and judicial power organized by the Constitutional Court.